Combine the reactions and take the sum of the ΔH applying Hess' Law
Hg(l) + Cl2(g) ⟶ HgCl2(s) ΔH = −224 kJ (reverse)
HgCl2(s) ⟶ Hg(l) + Cl2(g) ΔH = +224 kJ
Hg(l) + HgCl2(s) ⟶ Hg2Cl2(s) ΔH = −41.2 kJ (reverse)
Hg2Cl2(s) ⟶ Hg(l) + HgCl2(s) ΔH = +41.2 kJ
Combining the equations:
Calculate ΔH for the process Hg 2Cl2(s) ⟶ 2Hg(l) + Cl2(g) from the following information:
Hg(l) + Cl2(g) ⟶ HgCl2(s) ΔH = −224 kJ
Hg(l) + HgCl2(s) ⟶ Hg2Cl2(s) ΔH = −41.2 kJ
Frequently Asked Questions
What scientific concept do you need to know in order to solve this problem?
Our tutors have indicated that to solve this problem you will need to apply the Hess's Law concept. You can view video lessons to learn Hess's Law. Or if you need more Hess's Law practice, you can also practice Hess's Law practice problems.
What professor is this problem relevant for?
Based on our data, we think this problem is relevant for Professor Dixon's class at UCF.
What textbook is this problem found in?
Our data indicates that this problem or a close variation was asked in Chemistry - OpenStax 2015th Edition. You can also practice Chemistry - OpenStax 2015th Edition practice problems.